Arsenophonus symbiosis with louse flies: multiple origins, coevolutionary dynamics, and metabolic significance - Martin Říhová, Jana; Gupta, Shruti; Darby, Alistair C; Nováková, Eva; Hypša, Václav (mSystems, 2023)
Insects that live exclusively on vertebrate blood utilize symbiotic bacteria as a source of essential compounds, e.g., B vitamins. In louse flies, the most frequent symbiont originated in genus Arsenophonus, known from a wide range of insects. Here, we analyze genomic traits, phylogenetic origins, and metabolic capacities of 11 Arsenophonus strains associated with louse flies. We show that in louse flies, Arsenophonus established symbiosis in at least four independent events, reaching different stages of symbiogenesis. This allowed for comparative genomic analysis, including convergence of metabolic capacities. The significance of the results is twofold. First, based on a comparison of independently originated Arsenophonus symbioses, it determines the importance of individual B vitamins for the insect host. This expands our theoretical insight into insect-bacteria symbiosis. The second outcome is of methodological significance. We show that the comparative approach reveals artifacts that would be difficult to identify based on a single-genome analysis.
Keywords: symbióza; Enterobacteriaceae; coevolution; Anoplura; vitamin B komplex; Insecta; fylogeneze; Phylogeny; Bacteria; hematophagy; genome evolution; Animals; Vitamin B Complex; hmyz; zvířata; bacterial symbiosis; Symbiosis; Diptera; Gammaproteobacteria